CONCEPT OF CHILDREN’S DANCE COMPOSITION BASED TRADITIONAL GAMES IN ELEMENTARY SCHOOL - Ayo Sunaryo; Tati Narawati; Juju Masunah; Trianti Nugraheni (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
The composition is interpreted simply, namely regulating traditional dances, especially on floor patterns, directions, and level settings in the form of group dances. This dance composition is applied to prospective dance teachers to enhance their understanding and skills in dance composition, applied in creating children's dance compositions. The purpose of this paper is to discuss the techniques of dance composition of children in prospective dance teachers to make children's dance works. This article is the result of research using an experimental method. The qualitative paradigm is a method of discourse analysis to synthesize theories and concepts of dance composition from seven figures, namely: Brenda McCutchen, Anne Gilbert, Alma Hawkins, Jacqueline Smith, Larry Lavender, and Eko Suprianto. The concept of creating traditional children's game-based compositions can be used as teaching material for creating children's dance for prospective dance teachers in elementary schools.Keywords: traditional game, children's dance, composition